50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja - Meško, Gorazd; Ulčnik, Natalija (2025)
50 Years of the University of Maribor: Half a Century of Scholarship and Research. This scientific monograph, created to commemorate the significant anniversary of the University of Maribor, explores various aspects of its establishment, organization, and development, providing a comprehensive overview of the University's fifty-year journey as Slovenia's second-largest university. The intertwining of critical historical events, significant contemporary conditions, and an optimistic view of the future is thoughtfully encapsulated in eleven chapters. Emphasis is placed on the efforts leading to the establishment of the University, along with an overview of the legal foundations for its existence and organization. The spatial development of the University in relation to social, political, and urban resources is discussed, and trends in employee movements across different periods are highlighted. Educational activities and diverse study programmes are outlined, reflecting the community's needs. Additionally, this monograph examines scientific fields and research activities, evaluates research efficiency and competitiveness, and underscores the artistic traditions at the University of Maribor. It is dedicated to the students and their vital role within the university environment, and also addresses the University’s international cooperation and emphasizes the importance of strengthening internationalization. The sustainability of the University of Maribor is explored as part of its commitment to long-term competitiveness, with a forward-looking perspective on European integration, lifelong learning, digitalization, and the green transition. This monograph offers an important insight into the fifty-year existence of the University of Maribor and provides valuable data regarding its growth, impact, and establishment within the broader academic landscape.
Keywords: university founding; university development; higher education; scientific research activity; internationalization